Reflections on dance theatre: Insights and parallels - Zdravkova-Djeparoska, Sonja (Faculty of Dramatic Arts, 2019)
The need for classification, subordination and grouping sometimes imposes a serious task upon us, which on the one hand means forcing the performing arts into some frames and categories, but on the other hand it facilitates their interpretation, reading and decoding. Wanting to engage in one of the possible classifications, I referred to Peter Brook’s cult book The Empty Space, in which he distinguishes different types of contemporary theatre. Starting from there, but without an attempt to rigidly apply his types of theatre, this research yielded its own internal classification. The results have shown that theatre and its functions can fluctuate considerably within each category. Both polarities within each type show dramatically different features, purposes, receptions and reactions. Each of the three types defined here are supported by a suitable scientific instrumentarium and practically validated through appropriately selected performances which have been listed in the text.
Keywords: performance, dance, ballet, theatre.